Optimization of diagnostics of combat injuries of the abdomen - Herasymenko, O. S.; Shapovalov, V. Y.; Yenin, R. V.; Koshikov, M. A.; Haida, Y. I.; Herasymenko, S. D.; Muradyan, K. R.; Okolets, A. V. (Journal of Education, Health and Sport, 2021)
The aim - to optimize the diagnostic scheme for combat abdominal injuries at the II level of medical care by identifying the most informative and fast instrumental diagnostic methods. A clinical and statistical analysis of the results of surgical treatment of 496 wounded with combat abdominal injuries treated in military mobile hospitals from June 2014 to August 2017 was carried out. Additional diagnostic tests were conducted for the injured with BPH in the comparison groups - FAST protocol, laparocentesis and diagnostic laparoscopy. In the general array of the study (n = 496), the FAST protocol was performed by 208 wounded (41.9%), laparocentesis - 270 (54.4%), video laparoscopy - 103 (20.8%). The number of emergency ultrasound studies in the volume of the FAST protocol with combat abdominal injuries in group 1 was 19.2%, in group 2 - 40.7%, in group 3 - 66.5%. A more frequent FAST protocol for injured with BPG at level II of medical care in groups 2 and 3 resulted in a decrease in the number of laparocentesis performed from 68.3% (in group 1) to 38.6% (in group 3), and an increase in the number of video laparoscopic studies from 14.9% (in group 1) to 26.6% (in group 3), most of which turned into therapeutic laparoscopy. The data obtained indicate that the widespread introduction of the FAST protocol into the PID diagnosis scheme at the II level of medical care helps to reduce the number of invasive (often unfounded) methods, namely, laparocentesis and diagnostic laparotomy, reduce the time spent on diagnosis and the choice of optimal surgical tactics.